Survey of Nongovernmental Organizations Providing Pediatric Cardiovascular Care in Low- and Middle-Income Countries. (April 2014) - Nguyen, Nguyenvu; Jacobs, Jeffrey P.; Dearani, Joseph A.; Weinstein, Samuel; Novick, William M.; Jacobs, Marshall L.; Massey, Jeremy; Pasquali, Sara K.; Walters, Henry L.; Drullinsky, David; Stellin, Giovanni; Tchervenkov, Christo I.
Background: Nearly 90% of the children with heart disease in low- and middle-income countries (LMICs) cannot access cardiovascular (CV) services. Limitations include inadequate financial, human, and infrastructure resources. Nongovernmental organizations (NGOs) have played crucial roles in providing clinical services and infrastructure supports to LMICs CV programs; however, these outreach efforts are dispersed, inadequate, and lack coordination. Methods: A survey was sent to members of the World Society for Pediatric and Congenital Heart Society and PediHeart. Results: A clearinghouse was created to provide information on NGO structures, geographic reach, and scope of services. The survey identified 80 NGOs supporting CV programs in 92 LMICs. The largest outreach efforts were in South and Central America (42%), followed by Africa (18%), Europe (17%), Asia (17%), and Asia-Western Pacific (6%). Most NGOs (51%) supported two to five outreach missions per year. The majority (87%) of NGOs provided education, diagnostics, and surgical or catheter-based interventions. Working jointly with LMIC partners, 59% of the NGOs performed operations in children and infants; 41% performed nonbypass neonatal operations. Approximately a quarter (26%) reported that partner sites do not perform interventions in between missions. Conclusions: Disparity and inadequacy in pediatric CV services remain an important problem for LMICs. A global consensus and coordinated efforts are needed to guide strategies on the development of regional centers of excellence, a global outcome database, and a CV program registry. Future efforts should be held accountable for impacts such as growth in the number of independent LMIC programs as well as reduction in mortality and patient waiting lists.